Sixth Meeting of the National Development Council Summary Record New Delhi: January 1956 - Planning Commission (Planning Commission, Government of India, 1956)
The Sixth Meeting of the National Development Council, held in New Delhi on January 20–21, 1956 under the leadership of Jawaharlal Nehru, marked a decisive stage in shaping the framework of the Second Five-Year Plan and articulating India’s long-term development vision centered on establishing a socialistic pattern of society. The deliberations emphasized inclusive and flexible planning, expansion of the public sector—particularly heavy industry and machinery manufacturing—strategic resource mobilization, and careful consideration of deficit financing, taxation reforms, and foreign assistance to sustain ambitious outlays. Participants, including key figures such as Finance Minister C. D. Deshmukh and regional leaders like P. Govinda Menon, highlighted the urgency of addressing regional disparities through balanced development, improved rural infrastructure, technical education, and cooperative sector expansion. The proposal for balanced regional development underscored the need for measurable indicators of progress, equitable allocation of resources, colonization of sparsely populated areas to mitigate unemployment, and reforms targeting landless agricultural laborers through cooperative farming and land policy adjustments. A recurring concern was that growth should elevate minimum living standards across all regions rather than disproportionately benefit already developed areas. Collectively, the meeting reinforced the principle that coordinated state-level collaboration, fiscal discipline, industrial prioritization, and cooperative institutional frameworks were essential to achieving equitable socio-economic transformation and sustained national progress.
Government of India Planning Commission
Keywords: Sixth National Development Council Meeting; Second Five-Year Plan; Socialistic Pattern of Society; Public Sector Expansion; Deficit Financing; Resource Mobilization; Balanced Regional Development; Cooperative Farming; Land Reform Policy; Technical Education and Training; Regional Disparities; State-Level Collaboration